Kontestasi Pasangan Suami Istri dalam Pilkades - Puji Astuti; Sulistyowati Sulistyowati; Lusia Astrika (JPW (Jurnal Politik Walisongo), 2019)
The Act Number 6 of 2014 cause of a great implication especially on the election of village chief. More over regarding on Ministerial Regulation Number 112 Year of 2014, article 23, which prohibit the single candidate opposing with the empty of ballot box. Thus, prohibition emerging of interesting phenomenon where is 17 couples of husband and wife being contestant on the village chief election in Demak Regency in the year of 2016. The aims of the reserch is to comprehend the husband’s reason to choose his wife as associate candidate. Do thus fact be part of practicing of women subordination? How the influence of thus phenomenon to the villlage democracy itself? The research uses qualitative-descriptive method with depth interview as instrument in collecting data. The result show that there are two main husband’s reason choose his wife as a competitor. Fisrt, by choosing his wife mean that there is no cost for compensation and no hard worry about conflict of interest in the coming day after election. Second, becoming his wife as a competitor mean that the winning opportunity is greater because patriarchy and Islamic tradition (were more joy in placing men as a leader) in Demak Regency. Then, the emerging of husband and wife as a candidate would decrease of democracy because there no rivalry as a soul of democracy. To improve of village chief election as a source of village democracy, it is best to correct the regulation which prohibit of the a single canditate by completing with require that the village chief election should be follow by at least two candidate who both of them have no relation as nuclear family.